Incidence of in-hospital all-cause mortality, resource utilization and complications in patients with adult congenital heart disease undergoing TAVR-a national inpatient sample study. (3rd October 2022) - Hajra, A; Patel, N; Bandyopadhyay, D; Chakraborty, S; Goel, A; Gupta, R; Amgai, B; Malik, A
Abstract: Background: The prevalence of congenital heart disease (CHD) in adults in the United States is approximately 1.4 million. (1) With the advancement in diagnostic modalities and advanced treatments, including minimally invasive techniques, the life expectancy of individuals with CHD has greatly improved. (2) As these patients enter the 8th decade of their lives, the risk of calcification and aortic stenosis increases like the population without CHD. Current evidence supports transcatheter aortic valve replacement (TAVR) over surgical aortic valve replacement in individuals with moderate to high surgical risk. (3) Adults with acyanotic CHD (ACHD) with a higher risk for surgical complications are candidates for consideration of TAVR. There are sparse data about the cardiovascular outcome in these patients. Purpose: With this National inpatient sample (NIS) study, the authors have shown the incidence of in-hospital all-cause mortality, resource utilization, and complications in adult patients with ACHD undergoing TAVR. Methods: NIS 2016–2018 were utilized to conduct the study. Analyses were performed using STATA, version 16.0. Using appropriate ICD-10-PCS codes, authors identified adult patients with ACHD undergoing TAVR. The primary outcome of the study is to identify the impact of ACHD on all-cause in-hospital mortality and complications. Secondary outcomes of interest were resource utilization. Results: 134, 170 patients were identified who had TAVR done between 2016–2018. Patients aged ≤18 years were excluded (N=25). Out of 134, 170 patients that underwent TAVR, 1, 170 (0.87%) were noted to have ACHD. Using the greedy algorithm, 1, 115 matched pairs were generated. The ACHD group had a higher burden of co-morbidities including atrial fibrillation (46.2% vs. 38.8%, p=0.016), pulmonary hypertension (27.4% vs. 17.5%, p<0.001), metabolic syndrome (1.3% vs. 0.3%, p=0.005), peripheral vascular disease (29.5% vs. 24.1%, p=0.049), alcohol use disorder (3.0% vs. 1.3%, p=0.018), coagulation disorder (22.7% vs. 12.8%, p<0.001), drug abuse (1.3% vs. 0.4%, p=0.043), liver disease (7.3% vs. 3.1%, p<0.001) and electrolyte disturbances (20.5% vs. 14.9%, p=0.017). We also noted a possible trend towards higher complication odds (cardiac complications such as the need for pericardial drain or cardiac implantable electronic device and cardiac arrest) in patients with ACHD undergoing TAVR without statistical significance based on multivariate analysis. On propensity matching, no difference was found in the incidence of overall cardiac complications between patients with ACHD and patients without ACHD, except STEMI (OR 4.16, 95% CI, 1.08–16.00, p=0.038). Conclusion(s): The study points towards the possible safety of pursuing TAVR in ACHD patients provided adequate technical support and operator competency. Funding Acknowledgement: Type of funding sources: None.